35 Years on the Road from Research to Practice: A Review of Studies on Four Content Enhancement Routines for Inclusive Subject‐Area Classes, Part II. Issue 3 (14th September 2021) - Fisher, Joseph B.; Schumaker, Jean Bragg
Abstract: This article is the second part of a two‐part article focusing on research that has been conducted on Content Enhancement Routines, instructional routines developed to be used during inclusive subject‐area instruction. Part I of this article (Schumaker and Fisher, 2021) reviews the original validation studies that were conducted on four Content Enhancement Routines. This second part of the article reviews 10 empirical studies that have been conducted comparing the effects of two professional development methods (i.e., a computerized workshop and a live workshop) for instructing teachers to use the same four teaching routines. In every study, teacher knowledge of the routine and teacher preparation for using the routine were measured. In four of the studies, teacher implementation of the routine within inclusive classes as well as student performance were also measured. Results were reported for the whole group of students in all four studies, and for students with LD in three of the studies. In all of the studies, teachers made large and significant gains in performance on all measures after both workshop conditions, representing large effect sizes. All in‐service teachers performed the routine at a high level of quality in their classes after 3 hours of instruction. In two studies, the teachers who participated in the computerized instruction earned significantly higher implementation scores than the teachers who participated in the live instruction. Regarding student performance across the studies, the whole group of students and the students with LD earned significantly higher scores on the posttests than on the pretests for both groups of teachers, again representing large effect sizes. Additionally, in two studies, the whole groups of students whose teachers used the software earned significantly higher scores on posttests than the whole groups of students whose teachers participated in live sessions. These studies replicate and extend the studies reviewed in Part I of this article; they show that quality teacher use of four Content Enhancement Routines results in increases in performance for all students, and for students with LD in inclusive classes.